2020
DOI: 10.1186/s12960-020-00474-y
|View full text |Cite
|
Sign up to set email alerts
|

Why do graduates choose to work in a less attractive specialty? A cross-sectional study on the role of personal values and expectations

Abstract: Background: Primary health care (PHC), of which preventive medicine (PM) is a subspecialty, will have to cope with a deficiency of staff in the future, which makes the retention of graduates urgent. This study was conducted in Vietnam, where PM is an undergraduate degree in parallel to medical training. It aims to identify facilitating and hindering factors that impact recruitment and retention of PM graduates in the specialty. Methods: A cross-sectional study enrolled 167 graduates who qualified as PM doctors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…For example, physicians working in rural Kenya and Benin feel more comfortable and confident with their work taking short training courses, with about 20% of them mentioning an increase of interest and work commitment [ 31 ]. This effectiveness of CME on satisfaction and retention of physicians working in LASs is also reported in other countries [ 34 – 39 ]. Considering that training programs for physicians in LASs, including in-service training or continuing education, are often not available [ 40 – 43 ], there is a need for information on how CME can be designed and implemented to increase physicians’ motivation to work in LASs.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…For example, physicians working in rural Kenya and Benin feel more comfortable and confident with their work taking short training courses, with about 20% of them mentioning an increase of interest and work commitment [ 31 ]. This effectiveness of CME on satisfaction and retention of physicians working in LASs is also reported in other countries [ 34 – 39 ]. Considering that training programs for physicians in LASs, including in-service training or continuing education, are often not available [ 40 – 43 ], there is a need for information on how CME can be designed and implemented to increase physicians’ motivation to work in LASs.…”
Section: Introductionsupporting
confidence: 80%
“…Another demotivating factor is that physicians in LASs have fewer opportunities to participate in continuing medical education (CME) activities, such as classes, seminars, and training, to update their knowledge and extend skills in their field. Indeed, CME is considered an important factor motivating doctors to work in LASs [7,10,34], as it significantly improves satisfaction, learning, performance, and specialist recertification in LASs physicians [30][31][32][33]. For example, physicians working in rural Kenya and Benin feel more comfortable and confident with their work taking short training courses, with about 20% of them mentioning an increase of interest and work commitment [31].…”
Section: Introductionmentioning
confidence: 99%
“…7 It even revealed that responsibility for taking care of parents motivated male graduates at one Vietnamese medical school to choose a medical specialty more attached to family and the community. 64 Or, the female students in our study just too young having no spouses or family responsibilities yet so that their NWLB would not have caused their perceptions to differ from those of male students.…”
Section: Discussionmentioning
confidence: 83%
“…Community medicine is often perceived as less prestigious, less challenging and less innovative than hospital medicine 1 [ 16 ]. In less prestigious fields of medicine, physicians face lower reputation, higher workload, feelings of professional isolation, limited career development opportunities and high burnout [ 17 , 18 ]. These, in turn, may affect professional identity and make doctors less satisfied and less likely to stay in their position, which leads to health service workforce imbalances and suboptimal health outcomes, especially in primary care areas such as pediatrics [ 16 ].…”
Section: Introductionmentioning
confidence: 99%